(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Currently, high-grade cotton makes up 80-85% of the raw cotton grown in our Republic. This, in turn, is one of the urgent issues of drying and cleaning high-grade cotton with preservation of natural quality indicators in special new modern low-energy drying and cleaning equipment. The drying of high-grade cotton in the currently used 2SB-10, SBT, SBO drying drums leads to high energy consumption, which is one of the main reasons for the twisting of cotton. Therefore, the study of the main factors influencing the high efficiency of drying and cleaning of high-grade raw cotton in special new equipment is considered an urgent task